Erscheinungsformen und Handhabungen heiliger Schriften: [Workshop mit dem Titel „Erscheinungsbild und Handhabung Heiliger Schriften“ vom 25. bis zum 27. November 2011 im Internationalen Wissenschaftsforum der Universität Heidelberg (IWH)] - Quack, Joachim Friedrich; Luft, Daniela C. (Materiale Textkulturen, 2014)
This study focuses on Holy Scriptures as material objects. What are the contexts for the appearances and the usages of these objects? Is there a difference between Holy Scriptures and other objects, and is it inevitably their sacred content that renders them holy? Interdisciplinary perspectives offer new incentives for understanding the material phenomenon of the 'Holy Scriptures'.--
Literaturangaben
Keywords: Konferenzschrift -- 2011 -- Heidelberg; Entstehung; Buch; Heilige Schrift; Geschichte; Materialität; Schriftlichkeit; Heiligkeit